Surface Roughness after Milling of the Al/CFRP Stacks with a Diamond Tool - Elżbieta Doluk (MDPI AG, 2021)
This study presents the results of research on the surface quality of hybrid sandwich structures after milling with a diamond blade tool. It identifies the effects of feed and machining strategy on the roughness and topography of the surface. It provides an analysis of Ra and Rz surface roughness parameters as well as Sp, Sz, and Sv surface topography parameters. The processed object was a two-layer sandwich structure consisting of aluminium alloy 2024 and CFRP (carbon fibre-reinforced polymer) composite. The minimum values of the Ra and Rz surface roughness parameters were obtained on the aluminium alloy surface, whereas the maximum values were obtained on the CFRP surface. The same was true for the 3D surface roughness parameters—the lowest values of Sp, Sz, and Sv parameters were obtained on the surface of the metal layer, while the highest values were obtained on the surface of the composite layer (the maximum value of the Sp parameter was an exception). A surface topography analysis has revealed a targeted and periodic pattern of micro-irregularities for the vast majority of the samples considered. The statistical analysis shows that the surface roughness of the aluminium alloy was only affected by the feed rate. For the CFRP, the feed rate and the interaction of milling strategy and feed rate (S <semantics>×</semantics> fz) had a statistically significant effect. The obtained results provide a basis for designing such sandwich element processing technology, for which differences in roughness and topography parameters for the component materials are lowest.